NTERACTION DESIGN OF FEATURES THAT SUPPORT EFFECTIVE FORMATIVE FEEDBACK ON ASSIGNMENTS IN MICROSOFT TEAMS - Rafi Zhafran, Muhammad
Feedback is a part of the learning process that is important to be done because it could increase student achievement and helps students in knowing their current understanding of the subject. The current implementation of feedback that hasn’t been done effectively and how the effective feedback is being unsupported by the many online learning application is regarded as the primary problem that wanted to be solved by this final project. The final project that’s built using goal-directed design (GDD) methodology as a part of user-centered design approach makes the goal of teachers in giving effective feedbacks and the goal of students in receiving effective feedbacks as the primary focus of the project. The phases of GDD that are being implemented in this project are research, modeling, requirements definition, interactions definition, and refinement. The research phase will generate design goals that are going to be examined in the refinement phase, general requirements, and user goals and tasks. The modeling phase will generate some personas that are going to be referred to while building the design. The requirement definition phase will generate a list of features, and the usability and UX goals that are aimed to be achieved by the interaction design produced by this project. The interaction definition phase will generate some low-fidelity prototypes. The refinement phase will generate some tested high-fidelity prototypes. The usability and UX goals that are aimed to be achieved by this project are effectiveness, efficiency, learnability, and helpfulness. The final result of this project is a high-fidelity prototype that’s built using Figma. The testing of the high-fidelity prototype is measured using completion rate to measure its effectiveness, overall relative efficiency to measure its efficiency, system usability scale to measure its general usability, single ease question to measure its learnability, and intrinsic motivation inventory to measure its helpfulness. The result of the testing of the high-fidelity prototype shows that the prototype has achieved the design goals, and the mentioned usability and UX goals.